Об’єкти промислово-комунальної архітектури і програма їх реабілітації - Іванов-Костецький, Сергій (Видавництво Національного університету «Львівська політехніка», 2009)
On an example of L’viv it is considered the general typological town-planning characteristics of objects of industriallymunicipal architecture of the end XVIII - the XX-th century beginnings. It is offered means of architectural rehabilitation methods focused on preservation and restoration of valuable composite and town-planning structure of a historical city.
Keywords: architectural rehabilitation; industrially-municipal architecture; industrial architecture